Pengaruh Discharge Planning Model Lima Terhadap Kesiapan Pulang Pasien di Ruangan Rawat Inap Rumah Sakit TK II Robert Wolter Mongisidi Manado - Silvia Dewi Mayasari Riu; Norman A. Talibo (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Discharge planning needs to be implemented from the time the patient enters the hospital until the day of discharge. Providing effective information can increase the knowledge and skills of patients and families to carry out independent care at home which is assumed to be ready for discharge so that it is hoped that rehospitalization events will not occur. This study aims to see whether there is an influence of Discharge planning model five on readiness to go home and family. The research design used a quasi experiment with a two group pre and post test using a purposive sampling approach carried out on inpatient students. The research instrument used the Readiness For Hospital Discharge Scale (RHDS) questionnaire. Data analysis used the Paired T test. The results of research on 30 respondents using the Independent T test on the average readiness to go home after (posttest) patients in the Intervention and Control groups obtained P value = 0.000 < ? (0.05) there was a difference in the average stress after (posttest) in the Intervention group with the control group. Based on this research, Discharge planning model five is able to increase patient readiness to go home and it is hoped that it can provide input to hospitals so that they can make Discharge planning model five as a method that can be given to patients when the patient is admitted until the patient wants to prepare to go home.